Changes in global trade patterns and women's employment in manufacturing: An analysis over the period of Asianization and deindustrialization - Burça Kızılırmak; Emel Memiş; Şirin Saraçoğlu; Ebru Voyvoda (Levy Economics Institute of Bard College, 2014)
The purpose of this study is to explore the employment effects of changes in manufacturing output resulting from shifting trade patterns over the period 1995-2006. For 30 countries (21 OECD and 9 non-OECD countries) we estimate the changes in embodied labor content due to trade using factor-content analysis, breaking up the sources of these changes between trade with the North, the South and China. We also decompose changes in employment into its component changes within and across sectors. Our results present a net negative impact of trade on total employment in 30 countries over the period of analysis (despite employment gains in 17 countries). Except for the Philippines and the Republic of Korea, trade with China has a negative impact on total employment in all countries, with a stronger negative effect on women's employment. Employment losses in the South due to a surge in imports from China are coupled with declining exports to the North, as many countries in the North shift their imports to emerging economies in Asia. Decomposition results indicate that the decline in the share of women's employment is mainly due to shifts between sectors rather than changes within sectors. Changes in women's employment are still highly dependent on movements in "traditional" manufacturing sectors, including food, textiles, and wearing apparel.
Keywords: F16; J16; J21; 330; North-South trade; Decomposition Analysis; Factor Content Analysis; Gender Bias